2019
DOI: 10.18280/jesa.520501
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis on the Turning of Aluminum Alloy 7075 Based on Taguchi Method and Artificial Neural Network

Abstract: This paper mainly aims to disclose the effects of cutting conditions on the turning of aluminum alloy 7075 (AA7075). First, the artificial neural network (ANN) was programmed to investigate how cutting parameters, namely cutting speed, feed rate and depth of cut, affect the surface roughness of AA7075. Then, the taguchi method was introduced to design an L 27 orthogonal array, in which each cutting parameter is considered on three levels. The results of orthogonal analysis were used to train the ANN called bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Experiments were conducted as per Taguchi's L27 orthogonal array [21,22] and detailed as in Table 4. Spindle speed (s), feed rate (f) and axial depth of cut (d) are the input process parameters and surface roughness (Ra) is the output response.…”
Section: Experiments Detailsmentioning
confidence: 99%
“…Experiments were conducted as per Taguchi's L27 orthogonal array [21,22] and detailed as in Table 4. Spindle speed (s), feed rate (f) and axial depth of cut (d) are the input process parameters and surface roughness (Ra) is the output response.…”
Section: Experiments Detailsmentioning
confidence: 99%
“…They concluded that the feed rate was the most important factor followed by cutting speed and approach angle. Joshy et al [16] performed CNC turning operation on the material of aluminum alloy 7075 and the surface roughness was conducted by considering machining parameters like feed rate, depth of cut, and spindle speed. The optimization of the process was carried out utilizing "analysis of variance (ANOVA)".…”
Section: Introductionmentioning
confidence: 99%